ANALISIS PUTUSAN MENGENAI PERKARA PERDATA YANG DIPERIKSA BERDASARKAN HUKUM ACARA PIDANA: Analysis Of Decisions On Civil Cases Examined Based On Criminal Procedure Law - Dava Setiawan Hanif; Elfrida Ratnawati Gultom (Faculty of Law, Universitas Trisakti, 2024)
The purpose of this thesis research is to analyse Decision Number 611/Pid.B/2023/PN Jkt.Tim, in which the defendant was convicted of fraud, then the judge convicted the defendant because he had committed fraud legally and convincingly, then the defendant had violated the contents of the agreement accompanied by bad faith. The main issues raised are whether the actions of the defendant in Decision Number 611/Pid.B/2023/PN Jkt. Tim include criminal acts? And whether the Judge's consideration in Decision Number 611/Pid.B/2023/PN Jkt.Tim was appropriate? The method used in writing this thesis is normative research with descriptive research supported by secondary data, sourced from primary, secondary, and tertiary legal materials. Based on the analysis conducted, the result and it can be concluded that the defendant's actions in verdict Number 611/Pid.B/2023/PN Jkt.Tim. Not a criminal act because there are no criminal elements found in the defendant's actions, not even including default on the coal sale and purchase agreement and the consideration of Judge Number 611/Pid.B/2023/PN Jkt.Tim. This decision was incorrect because it did not look at the basis of the Defendant's actions, as well as assessing the Police Investigation Report and the facts during the trial at the Court.